The Analysis of Production and Income of Lift Net in Kaleroang Village, South Bungku Sub District, Morowali District - Ruslan, Ruslan; Limi, Muhammad Aswar (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
This study aims to analyze the production, income, and feasibility of Lift Net In Kaleroang Village, South Bungku Sub District, Morowali District. The research was conducted in February 2020 in the waters of Kaleroang Village. Data collection was carried out by direct interviews with respondents using a questionnaire. The population and sample in this study were all fishermen who worked on floating charts in Kaleroang Village, Bungku Selatan Sub District, with as many as 20 fishermen. Data analysis using production analysis, income, and RC ratio analysis. The results showed that the average monthly production of Lift Net in Kaleroang Village was 5,697 kg / month with an average Income of IDR 12,079,583 / month and an RC ratio of 6.58, which means a floating chart business is feasible to develop.